2012
DOI: 10.1016/j.ajpath.2012.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin and Skeletal Muscle

Abstract: Upregulation of muscular adiponectin could act as a local protective mechanism to counteract cellular damage in obesity by weakening inflammation, oxidative stress, and apoptosis. To test this hypothesis, adiponectin-knockout (KO) and wild-type (WT) mice were fed a Western diet (WD). WT mice under WD conditions displayed 63% higher adiponectin expression in myocytes than those under standard laboratory diet (SLD) conditions (P = 0.011). WD-fed KO mice exhibited approximately threefold larger myocyte degenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 33 publications
(72 reference statements)
3
34
0
Order By: Relevance
“…As AdipoR1 has been reported to mediate the autocrine effects of adiponectin (Jortay et al 2012, Patel et al 2012, our results indicate a role of E 2 in the enhancement of not only skeletal muscle adiponectin production but also of its local action. Moreover, the E 2 -mediated increase in Sirt1 expression at the mRNA level further supports the idea that this hormone could play a role in the stimulation of adiponectin signaling in skeletal muscle, given that Sirt1 is a downstream effector of the adiponectin signaling pathway that promotes PGC1a activation (Iwabu et al 2010), which induces an improvement in mitochondrial function and biogenesis.…”
Section: Discussionmentioning
confidence: 52%
“…As AdipoR1 has been reported to mediate the autocrine effects of adiponectin (Jortay et al 2012, Patel et al 2012, our results indicate a role of E 2 in the enhancement of not only skeletal muscle adiponectin production but also of its local action. Moreover, the E 2 -mediated increase in Sirt1 expression at the mRNA level further supports the idea that this hormone could play a role in the stimulation of adiponectin signaling in skeletal muscle, given that Sirt1 is a downstream effector of the adiponectin signaling pathway that promotes PGC1a activation (Iwabu et al 2010), which induces an improvement in mitochondrial function and biogenesis.…”
Section: Discussionmentioning
confidence: 52%
“…We have previously shown that in an environment of acute or chronic inflammation, ApN was overproduced in vivo by the “normal” mouse skeletal muscle to locally counteract excessive and deleterious inflammatory reactions [29, 30]. By contrast, the skeletal muscle of mdx mice was unable to overproduce local ApN {[18], data not shown}.…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin, also known as ACRP30, is secreted primarily by adipocytes, but is also expressed by cardiomyocytes and skeletal muscle [50]. Adiponectin improves insulin sensitivity and lipogenesis in adipocytes, and FA β-oxidation in myocytes and hepatocytes [9].…”
Section: Adipokinesmentioning
confidence: 99%